THE DYNAMICS AND POTENCY OF HALAL TOURISM IN SITUBONDO AS A CITY OF SANTRI - Faizul Abrori; Mustaqim Makki (Tasharruf: Journal Economics and Business of Islam, 2021)
Situbondo is the City of Santri. The three typologies of Situbondo tourism are nature tourism, cultural tourism, religious tourism and sports tourism. There are 83 destinations but none of them possess a brand as halal tourism. The purpose of this study is to analyze the dynamics and potential of halal tourism in Situbondo. This research is qualitative descriptive with a data analysis model using the Spradley model, where after determining the standards of halal tourism, it is followed by an inventory of the potential for halal tourism in Situbondo. The results of this study indicate that in Situbondo, although the tourism object does not have a brand as halal tourism, its implementation is in line with the sharia character, namely (1). Uluhiyyah, (2). Insaniyyah, (3). Akhlaqiyyah, and (4). Washatiyyah. There are three potentials for branding halal tourism in Situbondo: (1). Geographically, Situbondo is a north coast road, (2). The Even Kirap Culture of Ancak Agung and a spectacular Islamic New Year celebration, (3). The object of the Islamic Boarding School as an education center is both in quality and quantity.